2010
DOI: 10.1143/jpsj.79.083501
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Ni Nanoparticles Formation by Solution Glow Discharge

Abstract: We report the size control of Ni nanoparticles generated via solution glow discharge and focus on the effect of electrolyte concentration on Ni nanoparticles. In our experiments, voltage was applied to generate a plasma in NaOH electrolytes with concentrations ranging from 1.0 to 0.001 kmol m -3 . The applied voltage strongly depended on the electrolyte concentration, and interestingly, product size decreased with electrolyte concentration; for example, (mean diameter, applied voltage, electrolyte concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…NiNPs have been synthesized from discharge plasmas generated on a nickel cathode (immersed in H2SO4 [184], K2CO3 [123] and NaOH [125,185] solutions), and the NiNPs were observed in the solution as well as on the surface of the Ni cathode. The scanning electron microscope (SEM) image of NiNPs in the solution synthesized by Toriyabe et al [123] is shown in Fig.…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…NiNPs have been synthesized from discharge plasmas generated on a nickel cathode (immersed in H2SO4 [184], K2CO3 [123] and NaOH [125,185] solutions), and the NiNPs were observed in the solution as well as on the surface of the Ni cathode. The scanning electron microscope (SEM) image of NiNPs in the solution synthesized by Toriyabe et al [123] is shown in Fig.…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…As reported previously, 16,19,22,23 the experimental setup consisted of two electrodes in a glass cell with a capacity of 300 ml. The cathode consisted of a metal wire with a diameter of 1.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…When the full-plasma electrode was used, infrared radiation radiated continuously at the electrode edge (b), and plasma emission was also centered on the edge (c) plasma. 18,19,22 The particle size tends to decrease with an increase in the applied voltage. Additionally, the SEM observation of the electrode after electrolysis at different voltages, shown in Figs.…”
Section: B Effects Of the Electrolyte Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In addition, the size and composition of these nanoparticles can be controlled by changing the experimental conditions. 14,15 This method for producing nanoparticles has many advantages: (1) it requires a simple experimental setup without the need for a vacuum chamber; (2) there is no need to supply any gas; (3) a conductive electrode is used as the raw material, and harmful reductants or expensive agents are not required; and (4) it can be applied to any electrically conductive metal/alloy. To produce nanoparticles for various applications, control of the particle size and efficient production are essential.…”
Section: Introductionmentioning
confidence: 99%